TATA PERDAGANGAN PERIKANAN INDONESIA MELALUI INTRODUKSI STANDAR INTERNASIONAL SEAFOOD ECOLABELING - Nurshidiq, Rio Sena Eka; Anwar, Anwar; Benning, Bianca (Program Kreativitas Mahasiswa - Gagasan Tertulis, 2014)
Ecolabel is certification products give information to consumers that product life cycle in environmental effect negative a relatively small. World trade of fishery has shaded various provisions and regulation to keep the environmental sustainability (UNCLOS, CITES, act fishery). The arrangement trade fishery in Indonesia through a system of national logistics fish require useful aspect on this. Ecolabeling as one of the application of preserve the living environment more practical and interesting. Implementation seafood ecolabeling on trade fish in Indonesia can practiced on system logistics fish national which includes the application on fishing vessel, fish auction center, fish culture, fish processing and fish market. The application of ecolabelling manifested by sharing form model label the inspired, interesting and raises of awareness on the environment.Keywords: commercial fisheries, logistics environment, ecolabelling